Fibrin-VLDL Receptor-Dependent Pathway Promotes Leukocyte Transmigration by Inhibiting Src Kinase Fyn and is a Target for Fibrin β15-42 Peptide - Yakovlev, Sergiy; Cao, Chunzhang; Galisteo, Rebeca; Zhang, Li; Strickland, Dudley K.; Medved, Leonid (Thrombosis and Haemostasis, 2019)
According to the current view, binding of fibrin degradation product E1 fragment to endothelial VE-cadherin promotes transendothelial migration of leukocytes and thereby inflammation, and fibrin-derived β15–42 peptide reduces leukocyte transmigration by competing with E1 for binding to VE-cadherin and, in addition, by signaling through Src kinase Fyn. However, the very low affinity of β15–42 to VE-cadherin raised a question about its ability to inhibit E1–VE-cadherin interaction. Further, our previous study revealed that fibrin promotes leukocyte transmigration through the very-low-density lipoprotein (VLDL) receptor (VLDLR)-dependent pathway and suggested a possible link between the inhibitory properties of β15–42 and this pathway. To test such a link and the proposed inhibitory mechanisms for β15–42, we performed in vitro experiments using surface plasmon resonance, enzyme-linked immunosorbent assay, and leukocyte transendothelial migration assay, and in vivo studies with wild-type and VLDLR-deficient mice using mouse model of peritonitis. The experiments revealed that β15–42 cannot inhibit E1–VE-cadherin interaction at the concentrations used in the previous in vivo studies leaving the proposed Fyn-dependent signaling mechanism as a viable explanation for the inhibitory effect of β15–42. While testing this mechanism, we confirmed that Fyn plays a critical role in controlling fibrin-induced transendothelial migration of leukocytes and found that signaling through the VLDLR-dependent pathway results in inhibition of Fyn, thereby increasing leukocyte transmigration. Furthermore, our in vivo experiments revealed that β15–42 inhibits this pathway, thereby preventing inhibition of Fyn and reducing leukocyte transmigration. Thus, this study clarifies the molecular mechanism underlying the VLDLR-dependent pathway of leukocyte transmigration and reveals that this pathway is a target for β15–42.
Keywords: fibrinogen; fibrin; VLDL receptor; leukocyte transmigration; inflammation